Uniportal video-assisted thoracic surgery for major lung resections: pitfalls, tips and tricks - Ismail, Mahmoud; Swierzy, Marc; Nachira, Dania; Rückert, Jens C.; Gonzalez-Rivas, Diego (Journal of Thoracic Disease, 2017)
Nearly six years since inception, uniportal video-assisted thoracic surgery (VATS) has become a growing part of major lung resections and has revolutionized the way thoracic surgeons treat pulmonary lesions. This technique is being touted for various benefits. It ensures direct visualization together with a better exposure of the lung and allows the chance of a digital palpation of the lesion through a small incision. Postoperative pain is reduced due to the involvement of only one intercostal space without rib spreading and muscle disruption. The comfort and aesthetics factors are improved significantly since the oncological principles and radicality of open surgery are restored. As the surgeons gain more experience in uniportal-VATS lobectomy, more complex cases can be managed by this technique. The objectives of this work are to set the basic steps for performing major lung resections (lobectomy, bilobectomy and pneumonectomy) by utilizing uniportal-VATS and to analyze some common pitfalls that thoracic surgeons face when practicing this technique and provide practical tips and tricks on how to avoid.